1991
DOI: 10.1002/glia.440040607
|View full text |Cite
|
Sign up to set email alerts
|

Glial immunoreactivity for metallothionein in the rat brain

Abstract: A series of frozen and vibratome coronal sections of the rat brain were examined by immunocytochemistry for the presence of a cysteine-rich metal binding protein, metallothionein (MT). Astrocytes throughout the brain and brainstem stained positively for MT; neurons and oligodendroglia were unstained. Ependymal cells and tanycyte processes in the hypothalamus were also immunoreactive, along with a narrow zone of immunopositivity along the margins of the area postrema. Gomori-positive astrocytes in the hypothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 27 publications
5
35
0
2
Order By: Relevance
“…In accordance with the present study, most studies on MT expression in CNS describe the absence or scarcity of w x MT-immunopositive neurons 8,42,43,66 . On the other w x hand, by using polyclonal antibodies, Hidalgo et al 28 found MT immunoreactivity in neurons of different rat cerebral and cerebellar areas.…”
Section: Distribution Of Mt In Normal Animalssupporting
confidence: 91%
“…In accordance with the present study, most studies on MT expression in CNS describe the absence or scarcity of w x MT-immunopositive neurons 8,42,43,66 . On the other w x hand, by using polyclonal antibodies, Hidalgo et al 28 found MT immunoreactivity in neurons of different rat cerebral and cerebellar areas.…”
Section: Distribution Of Mt In Normal Animalssupporting
confidence: 91%
“…The findings agreed with those reported in the brain of humans [3,27,28], monkeys [26], rats [14,32] and mice [12,14]. Intense MT-I & -II immunoreactivity was observed in astrocytes in the periventricular area and those around the blood vessels, indicating that MT-I & -II may play a role as a barrier against the toxic substances including metals.…”
Section: Discussionsupporting
confidence: 90%
“…Immunohistochemical localization of MT-I & -II in the brain has been reported in humans [3,27,28], monkeys [26], mice [12,14] and rats [14,32]; MT-I & -II were shown in choroid plexus epithelial cells, ependymal cells, pia mater, and astrocytes in the hypothalamus, hippocampus, cerebral cortex and white matter throughout the brain. With at 5 µm were stained with hematoxylin and eosin (HE) and periodic acid methenamine silver (PAM).…”
Section: Animalsmentioning
confidence: 94%
“…Studies of in situ hybridization (21, 24-28) and immunohistochemistry (19,21,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), have demonstrated that MT-1&2 expression occurs throughout the brain and spinal cord, and that the principal cellular source is the astrocyte, particularly following injury. Significant MT-1&2 expression is also found in ependymal cells, epithelial cells of the choroid plexus, meningeal cells of the pia mater and endothelial cells of blood vessels, while neurons appear to express very low levels.…”
Section: Metallothionein-1and2 Are Preferentially Expressed In Reactivementioning
confidence: 99%